Improvement of Post‐Thaw Quality and In Vivo Fertility of Simmental Bull Spermatozoa Using Ferulic Acid - Mobin Afsar; Ali Soleimanzadeh; Amir Khaki; Esmail Ayen (Veterinary Medicine and Science)
ABSTRACT Background Artificial insemination and semen cryopreservation have significantly improved the quality and quantity of cattle production. Through cryopreserved semen and artificial insemination, top‐breeding bull sperm can be used to inseminate thousands of cows worldwide. Objectives Our study aimed to determine the effect of adding ferulic acid (FA) to a Tris‐based semen extender on frozen and thawed Simmental bull sperm. Methods Semen samples were collected from three Simmental bulls. Pooled Simmental semen (n = 34 ejaculations) were diluted with a Tris‐base extender containing varying FA concentrations (0.1, 0.15, 0.25, 0.35, and 0.45 mM). After the samples were frozen and thawed, the samples were tested for malondialdehyde (MDA), total antioxidant capacity (TAC), superoxide dismutase (SOD), glutathione peroxidase (GPx), total motility, progressive motility, motility characteristics, and plasma membrane functionality. Results The control and the groups with the best FA concentrations, 0.25 and 0.35, were compared for in vivo fertility. Fifty‐one cows were inseminated 24 h after the onset of oestrus. A rectal examination was used to diagnose pregnancies at least 60 days after fertilization. Results showed that adding FA‐0.45, FA‐0.35, FA‐0.25, and FA‐0.15 to the semen of Simmental bulls improved total and progressive motility, motility characteristics, and plasma membrane functionality. It also increased GPx and TAC levels, reducing MDA and DNA damage after freezing. The addition of FA did not affect SOD values. The fertility rate in the FA‐0.25 and FA‐0.35 groups was higher than in the control group, 35.29%, with rates of 76.47% and 70.58%, respectively. Conclusions In conclusion, adding FA (0.15, 0.25, 0.35, and 0.45 mM) to Tris‐based semen extenders can improve the quality parameters of cryopreserved Simmental bull semen and increase in vivo fertility using 0.25 and 0.35 concentrations of FA.